Impaired cellular and humoral immunity is a feature of Diamond-Blackfan anaemia; experience of 107 unselected cases in the United Kingdom. - Iskander,D; Roberts,I; Rees,C; Szydlo,R; Alikian,M; Neale,M; Harrington,Y; Kelleher,P; Karadimitris,A; de,la Fuente J (British Journal of Haematology, 2019)
Diamond-Blackfan anaemia (DBA) is a rare bone marrow failure syndrome characterised by anaemia, congenital anomalies and cancer predisposition. Although infections are the second leading cause of mortality in non-transplanted patients, immune function is largely unexplored. We identified quantitative deficits in serum immunoglobulins and/or circulating T, natural killer and B lymphocytes in 59 of 107 unselected patients (55·1%) attending our centre over a 7-year period. Immune abnormalities were independent of ribosomal protein genotype and arose in both steroid-treated and steroid-untreated patients. In summary, these data highlight the high prevalence and spectrum of infections and immune defects in DBA.